Reality Radio : Telling True Stories in Sound - Dilworth, Alexa; Biewen, John (Book collections on Project MUSE., 2010)
Over the last few decades, the radio documentary has developed into a strikingly vibrant form of creative expression. This volume celebrates today's best audio documentary work by bringing together some of the most influential and innovative practitioners from the U.S., Canada, the U.K., and Australia. In these 19 essays, documentary makers tell relate how they make radio the way they do, and why. Includes essays from Ira Glass, the Kitchen Sisters, Rick Moody, and producer Joe Richman, among others.